Sustainable Soybean Cultivation and Digital Marketing for Food Diversification in Sandy Soils - Gunadi, Hendrik; Alimuddin, Suraedah; Pasanda, Erna; Djunaidy, Machmud; Pala'langan, Agusanto; Adelia, Eunikke; Lebang, Adrian; Marsha; Lopang, Anugerah Andyni (LifeSciFi, 2025)
Sandy soil, low productivity, poor crop management, and limited marketing opportunities are the main challenges faced by soybean farmers in Jenetaesa Village, Maros Regency. The Langkasa and Langkasa Baru farmer groups collaborated with the team from Paulus Christian University of Indonesia to address these issues through a community service program. The program aimed to empower farmers by introducing sustainable soybean cultivation practices and innovations to support food diversification and better use of rainfed land during the dry season. The methods included socialization, practical training, field demonstrations, and ongoing mentoring. Farmers learned composting techniques using soybean waste, operating compost shredders and soybean threshers, the benefits of superior seeds, proper planting timing, and basic digital marketing to reach wider markets. The results showed increased farmer knowledge and skills in managing sandy soil, reducing post-harvest losses, and applying sustainable practices. Farmers began using compost to improve soil fertility, adopted mechanical threshers to minimize seed waste, planted superior varieties, and started exploring online marketplaces. The introduction of appropriate low-cost technologies proved effective in more productively utilizing sandy rainfed fields. The program not only enhanced soybean production and marketing but also contributed to household food security and economic improvement for the farming community.